A feasibility study on integrating the Philippine government documents collection of the University of the Philippines National College of Public Administration and the Governance library to the digital archives at UP Diliman - Dela Cruz, Terrence S.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
The UP NCPAG Library's Philippine Government Documents Collection holds great legal and cultural value due to the nature of its contents. However, the collection is, at the time of speaking, in very bad condition and lacks any preservation policies. This feasibility study explores the possibility of integrating the collection into the Digital Archives @ UP Diliman (DA@UPD) for the purpose of access and preservation.
This study has six factors that will determine the feasibility of the integration: the reception of UP NCPAG Library Management to the proposed integration, the reception of the DA@UPD to the proposed integration, the physical status of the collection, the submission policies that govern the collection, the information needs of the collection's Designated Community, and the assessment of the DA@UPD for OAIS compliance.
Both Managements are willing to push through integration. However, the DA@UPD declared that they would have to charge for digitization services. Alternatively, they suggested that the UP NCPAG Library digitize their collection on their own, and the rest of the integration can be executed by the DA@UPD for free.
The physical collection was found to be in poor condition, with most of the materials having suffered significant damage throughout the years. There are no preservation policies that govern the collection, nor any preservation copies and backups for each of the documents.
The documents were deposited into the library in compliance with Presidential Decree No 812, Decree on Legal and Cultural Deposit. Despite this, there are no known formal submission policies and agreements that govern the collection.
The collection's Designated Community, the UP NCPAG students, cite academic reference as the collection's most prominent use; these documents primarily function as reference for academic papers and research. The students also expressed desire in having the documents presented in text file format if the documents are to be integrated into a digital archive.
As the DA@UPD is a relatively new repository, assessment revealed it to be not fully OAIS-compliant; it has several key OASIS features missing. However, it is a functional digital archive that can accommodate the Philippine Government Documents Collection.
In conclusion, this study finds the proposed integration of the UP NCPAG Library's Philippine Government Documents Collection into the Digital Archives @ UP Diliman to be feasible.
Thesis
Keywords: University of the Philippines (Diliman) -- National College of Public Administration and Governance Library; Digital preservation; Digital libraries; Archival materials -- Digitization